The Variation of Productive Forces: Further Comment - Flux, A. W. (Quarterly Journal of Economics, 1904)
Journal Article The Variation of Productive Forces: Further Comment Get access A. W. Flux A. W. Flux University of Toronto Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 18, Issue 2, February 1904, Pages 280–286, https://doi.org/10.2307/1882789 Published: 01 February 1904